Modern Priyayi and The Failure of the Third Space in Kayam’s Two Fictions - Paulus Sarwoto (Universitas Sanata Dharma, 2023)
Umar Kayam’s fictions, “Kimono Biru” (Blue Kimono) and Jalan Menikung (Turning Road) retell rampant corruption plaguing most postcolonial states. The priyayi figuration in both stories, supposed to transform the third space of postcolonial Indonesia into liberative force, fails miserably. Rather than re-visiting positivist view of third space as found in many literatures, this analysis shows a re-imagination of its failure. The replacement of colonial leaders by domestic leaders does not guarantee true independence since the new middle class replicate the corrupt system for their own benefits. While corrupt priyayi thrives, the protagonist priyayi figures upholding potential transformative power in both fictions are rendered powerless in this newly independent state. Suwandi in “Kimono Biru” is an epitome of postcolonial politicians who are both politician and oligarch guarding the status quo – a system supported by money politics to manipulate the mass. Mustari, his old friend in fighting for independence from colonial Dutch, has to live a meagre live as the cost for maintaining his integrity. Similarly, in the priyayi in Jalan Menikung are also divided along similar lines. Sastradarsono’s posterity who chooses to be a corrupt military official (Nugroho) and a business tycoon (Tommi) live comfortably while those who side with the suffering mass have to live a difficult life because of their honourable idealism.